1992
DOI: 10.1346/ccmn.1992.0400514
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Synthetic Copper Phyllosilicates Studied by XPS

Abstract: Abstract--X-ray photoelectron spectroscopy (XPS) has been used to characterize the bonding state of Cu 2 § Si 4+, A13 § and 02 ions in structural (octahedral and interlamellar) or adsorbed position in phyllosilicates. Five smectites, 5 kaolinites, and 1 chrysocolla with Cu(II) in known positions (octahedral, interlamellar, or surface adsorbed) have been investigated. Their spectra were compared with those of pure Cu metal and of pure Cu(I) and Cu(II) oxides.The line for Cu 2p3/2 (binding energy of 935.4 eV) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 19 publications
(26 reference statements)
5
23
0
Order By: Relevance
“…XPS data for a powdered Brazilian chrysocolla have been reported by Mosser et al (1992), but the 4.2 eV Cu 2p 3/2 linewidth would have been too large to enable resolution of a minor component at $932.8 eV. Their Cu 2p 3/2 , O 1s and Si 2p binding energies were reported as 935.8, 532.3, and 102.8 eV, respectively.…”
Section: Chrysocolla Characterisationmentioning
confidence: 88%
“…XPS data for a powdered Brazilian chrysocolla have been reported by Mosser et al (1992), but the 4.2 eV Cu 2p 3/2 linewidth would have been too large to enable resolution of a minor component at $932.8 eV. Their Cu 2p 3/2 , O 1s and Si 2p binding energies were reported as 935.8, 532.3, and 102.8 eV, respectively.…”
Section: Chrysocolla Characterisationmentioning
confidence: 88%
“…A drop of that dispersion was placed onto a disk of 2-cm refractory vitreous carbon, air-dried and analyzed by XPS spectroscopy. The measurements were carried out after photoreduction times of 15 min, 2 h and 4 h according to the procedure described by Mosser et al (1992). Indeed, it was shown that photoreduction effects can differentiate structural Cu locations in clay minerals.…”
Section: Xps Measurementsmentioning
confidence: 99%
“…It has been proposed that this property of copper is not compatible with a regular clay structure Petit et al 1995). Octahedral sites occupied by Cu(II) in phyllosilicates are distorted, with Cu-O distances of 1.95 ,~ for the 4 in plan oxygens, and 2.32 .~ (in smectites) or 2.41 ,~ (in chrysocolla) for the 2 apical oxygens (Mosser et al 1990(Mosser et al , 1992. The Cu content of natural smectites is limited to about 2% (Mosser et al 1990;.…”
Section: Introductionmentioning
confidence: 99%